Vegetable lipids as components of functional foods. - Stuchlik, Milan; Zak, Stanislav (Biomedical papers, 2002)
Nutritionally beneficial compounds naturally present in vegetable lipids will be subject of this minireview. Thisarticle will discuss lipidic compounds from less known vegetable sources and potential advantages of its incorporationinto human diet as a functional ingredient.
Keywords: Lipids / Vegetable oils / Fatty acids / Fatty alcohols / Isoprenoids / Phytosterols / Tocopherols / Tocotrienols / Policosanols